Overview of animal behavior monitoring systems on the Ukrainian market with a brief description of their operating principles and technical characteristics - Slon, Yu.; Skliarov, P. (Scientific Progress & Innovations, 2025)
The aim of this publication is to review the main technologies used for detecting and signals related to estrus, calving, feed consumption, and the presence of diseases in dairy cattle. To achieve this, a search for proposals of advanced behavior change monitoring systems and relevant literature was conducted on the Google platform, in general and scientific publications, as well as through communication with representatives from farms and commercial companies (manufacturers and dealers of animal behavior monitoring systems). The review revealed that in modern animal husbandry, automated activity monitoring systems are widely used, which allow obtaining diverse information to improve herd management and increase animal productivity. The use of such devices simplifies the process of detecting estrus, calving, feed consumption, stress situations, and diseases, reducing the resources required for human observation and ensuring. The main devices available today use sensors such as accelerometers, pedometers, inclinometers, thermometers, and others, which are attached to animals to monitor their activity. Some researchers have also conducted studies using devices that do not require direct contact with animals, analyzing images from cameras, 3D cameras, and thermal cameras. There is demand for accessible and easily scalable technologies that can increase the profitability of animal husbandry by improving the management of reproductive processes (detecting animals in estrus, determining the exact time of insemination and calving), enabling early detection of sick animals and monitoring their treatment, managing feeding (by accurately detecting changes in feed consumption and rumination time), and understanding the effectiveness of climate control systems in livestock housing (stress levels in animal groups and body temperature). In conclusion, the market offers effective commercial systems for monitoring changes in cow behavior to detect behavioral changes in animals. By comparing the available technical characteristics of behavior monitoring systems, the COWMANAGER system, which is represented by an ear tag, stands out as the most comprehensive. It tracks the highest number of parameters, such as high activity, activity, rest time, feed consumption, rumination, and temperature. It has several independent and internal validation sources. The system includes additional equipment (a mobile station for locating animals or groups of animals in real-time, either indoors or on pasture) and features data exchange with herd management and breeding gate systems, with potential for further development. The notification function alerts about estrus status, insemination and calving time, feed and rumination time, stress and disease presence, and data visualization in the form of graphs enables the analysis of causes behind behavioral changes in animals.